Spectral characterization and quality assessment of organic compost for agricultural purposes - Anchal Sharma; Rajiv Ganguly; Ashok Kumar Gupta (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The study presents the physico-chemical, heavy metal and spectral characterization of aerobic compost to assess the suitability of its use for different purposes generated from two different municipal solid waste dumpsites located in the cities of Solan and Mandi in Himachal Pradesh. Methods The spectral characteristics of the compost material were determined using Scanning Electron Microscope (SEM), Energy Dispersive Spectroscopy (EDS) and X-ray Diffraction (XRD) technique. The heavy metal analysis of compost material was analyzed through atomic absorption spectroscopy (AAS). The study also focused on the determination of the qualitative nature of compost by utilizing an indexing method based on Fertilizer Control Order (FCO) Standards. The utility of the compost was characterized on the values of ‘Fertility Index’ and ‘Clean Index’. Results The Fertility Index (FI) of compost for Solan and Mandi was observed 3.5 and 3.6, respectively, whereas Clean Index (CI) of compost for both regions was observed 4.0 and 5.0 at the 60th day of sampling, respectively, with the former being classified as category D and the second being classified as category A of high fertilizing potential. Conclusions The MSW compost of Solan cannot be used as fertilizer due to its low fertilizing potential. The heavy metal concentration for the study regions has been found within the permissible limits of the fertility control order standards. It is concluded from the study that aerobic composting is a suitable option for processing of waste as well as it can reduce the weight of organic waste in the dumpsite.